2009
DOI: 10.1111/j.1365-2028.2008.01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Hunting, disturbance and roost persistence of bats in caves at Ankarana, northern Madagascar

Abstract: Surveys and monitoring of 37 caves in and around the Ankarana Special Reserve, northern Madagascar, yielded evidence of hunting of bats and potential disturbance of bats by miners and tourists, and colony counts for several bat species of potential conservation concern. Colony size decreased by 95% and 14% for a colony of Hipposideros commersoni and a colony of Eidolon dupreanum, respectively, when recent evidence of hunting occurred at those colonies and those declines are probably attributable to hunting. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…Because both species, Rousettus madagascariensis and Eidolon dupreanum , are capable of flying long distances, we used published estimates of their abundance at all roosts near Ankarana National Park [42], divided by the area of all primary and secondary forest in the same region [43].…”
Section: Methodsmentioning
confidence: 99%
“…Because both species, Rousettus madagascariensis and Eidolon dupreanum , are capable of flying long distances, we used published estimates of their abundance at all roosts near Ankarana National Park [42], divided by the area of all primary and secondary forest in the same region [43].…”
Section: Methodsmentioning
confidence: 99%
“…Concerns about the impact of cave tourism on Chinese bats have also been raised by Niu et al (2007) and Zhang et al (2009) and Olson et al (2011) also found that numbers of hibernating bats significantly increased in Cadomin cave, Canada after restrictions on visitors were enforced. In Madagascar, associations between tourism and hunting of cave-dwelling pteropodids were noted by Cardiff et al (2009) who speculated these might be due to improved access facilitating hunting activities when tourists are absent. Cardiff et al (2012) also analyzed the effects of tourism on the Malagasy rousette (Rousettus madagascariensis) and found that maintaining a minimum distance of 12 m between tourists and roosting bats and avoiding their illumination caused the least disturbance.…”
Section: Cave Tourismmentioning
confidence: 99%
“…Some insectivorous bat species are more light tolerant than others, such as the Seychelles sheath-tailed bat (Coleura seychellensis) which often roosts in open boulder caves (Bambini et al 2006), although light levels in these caves are not thought to be a major factor in roost selection. In contrast, Old World fruit bats (Pteropodidae) rely on vision and those species which roost in caves, such as E. dupreanum in Madagascar, do so within sight of the entrance (Cardiff et al 2009). Within this bat family, the genus Rousettus has evolved a form of echolocation involving clicking with its tongue and is capable of roosting deep in caves (MacKinnon et al 2003;Waters and Vollrath 2003).…”
Section: Influence Of Cave Microclimatementioning
confidence: 99%
“…The uniqueness of the island's biota and the magnitude of anthropogenic threat have led to its classification as one of the highest priorities for international conservation [23][24]. However, a combination of poverty, rapid population growth, insecure land-tenure, mining, hunting, agricultural expansion, and great demand for timber and charcoal production, poses a serious risk for much of the nation's remaining biodiversity [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%